SURFACE AREA DRIVEN CRYSTALLINITY CHANGES OF HYDROXYAPATITE DURING SIMULATED BODY FLUID IMMERSION - Agung Prabowo; Ahmad Fadli; Heni Sugesti; Muh Irwan (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2026)
The bioactivity of hydroxyapatite (HA) powders is strongly influenced by surface area and crystallinity. This study evaluates the effect of surface area and Ca/P ratio on the bioactivity of HA through immersion in simulated body fluid (SBF) for 3–21 days. Structural and chemical changes were analyzed using XRD, BET, SEM–EDX, and XRF, with bioactivity assessed from XRD peak intensity at 2θ ≈ 30°, degree of crystallinity, Ca/P ratio, calcium ion concentration, and pH variation. The results show that HA maintained its crystal phase during immersion, with the degree of crystallinity varying between 82% and 96%. An initial decrease in crystallinity and peak intensity indicated early HA dissolution, followed by an increase due to apatite layer formation at intermediate immersion times. Prolonged immersion resulted in reduced crystallinity, attributed to calcium depletion and partial re-dissolution. Higher surface area accelerated calcium ion consumption and enhanced apatite formation, confirming improved bioactivity of HA in SBF